Carbon Nanotubes Current Progress of their Polymer Composites - Reda Berber, Mohamed; Hazzaa Hafez, Inas (IntechOpen, 2016)
This book shows the recent advances of the applications of carbon nanotubes (CNTs), in particular, the polymer functionalized carbon nanotubes. It also includes a comprehensive description of carbon nanotubes' preparation, properties, and characterization. Therefore, we have attempted to provide detailed information about the polymer-carbon nanotube composites. With regard to the unique structure and properties of carbon nanotubes, a series of important findings have been reported. The unique properties of carbon nanotubes, including thermal, mechanical, and electrical properties, after polymer functionalization have been documented in detail. This book comprises 18 chapters. The chapters include different applications of polymer functionalization CNTs, e.g. photovoltaic, biomedical, drug delivery, gene delivery, stem cell therapy, thermal therapy, biological detection and imaging, electroanalytical, energy, supercapacitor, and gas sensor applications.